Aldo van Eyck - Orphanage Amsterdam building and playgrounds - Grafe, Christoph 1964-; Fischer, Suzanne; Álvarez Santana, Jaime; Otto, Laurens 1988-; Martens, Janno (Architectura & Natura, 2018)
In 1954 there existed in Amsterdam around 200 playgrounds designed by Dutch architect Aldo van Eyck, which in turn gave him the opportunity to design what is considered one of the most significant buildings in modern architectural history: the Amsterdam Orphanage. Completed in 1960, the building has been visited by numerous architects, among them Buckminster Fuller and Louis Kahn. Every detail, material, and colour of Van Eycks masterpiece, with its multiple pavilions, picturesque domes, and ingeniously linked patios, can be found in this richly illustrated book edited by Christoph Grafe
Keywords: Eyck, Aldo van -- 1918-1999; Architektur; Spielplatz; Waisenhaus; Amsterdam; Bildband